2015
DOI: 10.1155/2015/385127
|View full text |Cite
|
Sign up to set email alerts
|

The Anti‐Inflammatory Effect of Human Telomerase‐Derived Peptide on P. gingivalis Lipopolysaccharide‐Induced Inflammatory Cytokine Production and Its Mechanism in Human Dental Pulp Cells

Abstract: Porphyromonas gingivalis is considered with inducing pulpal inflammation and has lipopolysaccharide (LPS) as an inflammatory stimulator. GV1001 peptide has anticancer and anti-inflammation activity due to inhibiting activation of signaling molecules after penetration into the various types of cells. Therefore, this study examined inhibitory effect of GV1001 on dental pulp cells (hDPCs) stimulated by P. gingivalis LPS. The intracellular distribution of GV1001 was analyzed by confocal microscopy. Real-time RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…However, their biological characteristics in the reparative process under inflammatory microenvironment were not fully understood. LPS is usually used in the model of inflammation in vitro (Lee et al, ; Ko et al, ). To identify the proper concentration of LPS used for our study, the effect of various concentrations of LPS on the cell viability of NG2 + cells were tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their biological characteristics in the reparative process under inflammatory microenvironment were not fully understood. LPS is usually used in the model of inflammation in vitro (Lee et al, ; Ko et al, ). To identify the proper concentration of LPS used for our study, the effect of various concentrations of LPS on the cell viability of NG2 + cells were tested.…”
Section: Discussionmentioning
confidence: 99%
“…As the main component of the bacterial membrane, lipopolysaccharide (LPS) induces defensive inflammatory responses in the pulp (Bindal et al, ). In several experiments, LPS has been used to form a model of inflammation (Lee et al, ; Ko et al, ; Lertchirakarn and Aguilar, ). Upon LPS stimulation, stem cells of dental pulp play an important role in differentiating into odontoblasts to form new dentin (Tecles et al, ; Volponi and Sharpe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro culture studies using DPC (Ko et al . ), purified dental pulp SC (DPSC) populations (Li et al . ) and in vivo studies (Renard et al .…”
Section: Reviewmentioning
confidence: 99%
“…Dental pulp cells (DPCs) when challenged by the presence of a carious microbial biofilm will directly respond by expressing a range of genes and proteins, promoting defensive cellular processes such as cell migration, proliferation and differentiation (Farges et al 2015). Numerous in vitro culture studies using DPC (Ko et al 2015), purified dental pulp SC (DPSC) populations (Li et al 2014) and in vivo studies (Renard et al 2016) have demonstrated changes in cellular transcription and protein expression when inflamed. Furthermore, cells cultured in mineralizing, angiogenic and neurogenic culture conditions express a range of extracellular molecules, which promote an autocrine and paracrine healing response (Duncan et al 2013, Gervois et al 2015.…”
Section: Role Of Pulp Cells In Repairmentioning
confidence: 99%
“…Initially, this peptide was used for stimulating an immune response against several cancers in an injectable cancer vaccine and is currently found under clinical studies [ 48 , 49 , 50 ]. In addition to exhibiting potent anti-cancer activities as a drug, other important biological activities have been reported (e.g., antioxidant [ 51 ], anti-inflammatory [ 52 , 53 ] and antiviral [ 54 ]). Recently, the use of GV1001 have been reported as protection of stem cells by mimicking hTERT protein [ 55 ] Lee et al studied and characterized the cell entry mechanism of the peptide GV1001 [ 56 ].…”
Section: Chemical Modifications and Sirna Deliverymentioning
confidence: 99%